Mengelola Proses Peliputan Berita untuk Media Radio, TV, dan Daring - Winda Kustiawan; Fitrah Zico Amsari Nst; Muhammad Raihan; Rina Ashari Nasution; Nurhasanah Nurhasanah (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of information technology has brought significant changes in journalism practices and mass media management, particularly in radio, television, and online media. These changes have led to increased competition between media outlets and demands for ever-increasing speed in information delivery. This situation necessitates the implementation of effective editorial management to maintain news quality and credibility. This study aims to examine the implementation of news coverage and broadcasting management in radio, television, and online media, and to analyze the influence of differences in media characteristics on editorial management strategies. The study used a qualitative descriptive approach with a literature study method through analysis of various relevant literature sources. The results of the study indicate that editorial management plays a crucial role in controlling news quality through the implementation of planning, organizing, implementing, and monitoring functions. The differences in the characteristics of radio, television, and online media influence the process of managing news coverage, both at the pre-production, production, and post-production stages. Therefore, adaptive and systematic editorial management is a key factor in maintaining journalistic professionalism and public trust in the mass media.